A Compatibility in the Single Cell of the NiO/LSGM/LSCF - Atiek Rostika Noviyanti; Claudia Agesti; Yusi Deawati; Dani Gustaman Syarif (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2020)
The compatibility between anode, electrolyte, and cathode in a solid fuel cell determines its performance. Research on the compatibility between fuel cell components is challenging, especially for SOFCs that operate at high temperatures. Therefore, efforts to reduce the operating temperature to become intermediate temperature SOFC (IT-SOFC) are essential to facilitate compatibility between its components. La0.6Sr0.4Co0.2Fe0.8O3-δ (LSCF) has been recognized as one of the most promising cathode materials for (IT-SOFC) due to its high electronic conductivity and excellent electrical performance. While La0.8Sr0.2Ga0.8Mg0.2O3–δ (LSGM) has a high oxygen ion conductivity at low temperatures, its chemical stability is still not good. LSGM is known to have interface reactivity with other components such as NiO and LSCF in fuel cells. This study looked at the compatibility of NiO/LSGM/LSCF cells prepared by the solid chemical synthesis method. Compatibility evaluation is determined by the Thermal Expansion Coefficient (TEC) parameter using the dilatometric method, Area Specific Resistance (ASR), and TBF area morphology by Scanning Electron Microscope-Energy Dispersive Spectroscopy (SEM-EDS). While the conductivity of the cells is determined by Electrochemical Impedance Spectroscopy (EIS). NiO/LSGM/LSCF cells have good compatibility with a value of 78.05 kg-1.K.A.s3.µ2 at a temperature of 600°C. The ASR values of cells tend to decrease with increasing temperature and conductivity values at small TEC values. Based on these parameter values, delamination in NiO/LSGM/LSCF cells did not occur.